Analysis of soybean farmers income that involved and not involved in The Pajale Special Efforts Program (UPSUS). Issue 1 (April 2020) - Lanuhu, N; Saadah,; Mahyuddin,; Darwis,; Diansari, P; Sulili, A; Wirdansyah, A; Nurlaela,
Abstract: The UPSUS program (Special Efforts) is one of the efforts to support soybean self-sufficiency. Special Efforts (UPSUS) are the main program of the Ministry of Agriculture to improve the welfare of farmers. Through a special effort program (UPSUS), Pajale is expected to be able to be a learning material for farmers in increasing their farming production and productivity to increase the income and welfare of the farmer's family. This study aims to analyze the income of soybean farmers who are not involved and who are involved in the Special Efforts (UPSUS) Pajale program. The population of the study was 150 farmers who were involved in the UPSUS Pajale Program using the purposive sampling method. The analysis used in this study was income analysis by calculating the income, costs, and receipt of soybean farmers involved and not involved in the Special Efforts (UPSUS) Pajale program. The results of the study concluded that farmers who participated in Pajale's Special Efforts Program (UPSUS) had higher incomes than those who did not participate in the Pajale Special Efforts Program (UPSUS) in the three research sites.